Measuring tourist satisfaction and motivation: an investigation on visitors to Kuala Lumpur - Mohamad Noh, Mohamad Taufiq; Abdul Latif, Samshul Amry; Sawari, Siti Salwa (Cross Current Publisher, 2019)
This paper attempts to investigate the tourist satisfaction. The focus of the study is Kuala Lumpur, a well-known tourist destination in Malaysia. Questionnaires were distributed to 420 tourists. Descriptive statistic, factor analysis and multiple regressions were run on the 405 useable data. The results indicate the highest mean score is 3.95=for the tourist satisfaction. Tourist satisfaction is considered to be the key concept that drive the tourists to revisit certain place. Thus, the higher value for the tourist satisfaction could be a positive sign for the development. Besides that, for the satisfaction restoration, based on all N=405, the mean value is 3.89. On the other hand, the lowest mean value is the satisfaction- connectedness with only 3.53 which represent that youth tourist found out that they felt less sense of belongings towards the destination. The study has several implications for researchers, tour planners, travel related companies, and also government agencies when delivering service for the potential customers.